A study on relationship between service quality and customer satisfaction: a case study of TMNET customers, Melaka. / Siti Rahmah Abdol Rahim (Faculty of Business and Management, 2008)
This research is about a study on the relationship bet'Neen service quality and customer satisfaction in TMNET Melaka. Elements of reliability, tangibility and responsiveness of service quality have been identified in order to investigate whether or not these variables have relationship with customer satisfaction. The survey is conducted for TMNET customers. Those respondents come from various job specifications. There are 26 questions in the questionnaire and the sample size for this study is 120 respondents. Through out the survey, only 100 questionnaires were returned. Data obtained using two methods that are primary and secondary data. The primary data was questionnaire that required the respondents to answer the questionnaire that contain elements which potentially have relationship with customer satisfaction. In this study, data are analyzed using reliability test, frequency analysis, and ANOVA test analysis through SPSS Program. The result of this study showed that only two out of three from independent variables were significant which are reliability and tangibility has a significant relationship with the customer satisfaction. Meanwhile responsiveness has no significant relationship with customer satisfaction.